Explanation: When multiplying binomials that are in the pattern of (x + y)(x - y) the product is in the form of x² - y². The answer is the subtraction of the squares of the terms, or the "difference of squares". The product of (x + 4)(x - 4) becomes x² - 4.

Examples:

(x + 8)(x - 8) = x * x + (-8) * x + + 8 * x + 8 * (-8) = x² + (-8x) + 8x + (-64) = x² - 64

(x + 7)(x - 7) = x² + (-7x) + 7x + (-49) = x² - 49

(x + 5)(x - 5) = x² - 25

Directions: Each problem will fit the pattern shown above, known as the "difference of squares". Strive to be able to accomplish the problems with ease and then strive for increasing your speed. Good luck and enjoy the challenge!